Closed Int Soft -Ideals and Int Soft c--Ideals - Young Bae Jun; Kyoung Ja Lee; Eun Hwan Roh (Journal of Applied Mathematics)
The aim of this paper is to lay a foundation for providing a soft algebraic tool in considering many problems that contain uncertainties. In order to provide these soft algebraic structures, the notions of closed intersectional soft -ideals and intersectional soft commutative -ideals are introduced, and related properties are investigated. Conditions for an intersectional soft -ideal to be closed are provided. Characterizations of an intersectional soft commutative -ideal are established, and a new intersectional soft c--ideal from an old one is constructed.